Erectile dysfunction after COVID-19 infection: A cross-sectional study in a male sample from Brazil - Bressa, Gabriel Marton; Lopes, Vinicius Eduardo; Machado, Vinicius Buturi; Arbigaus, Cesar Alexsandro; Santos, Matheus Caires dos; Silveira, Ricardo Mendes; Sobreiro, Bernardo; Skare, Thelma; Nisihara, Renato (ABCS Health Sciences, 2024)
Introduction: COVID-19 infection may cause erectile dysfunction due to local viral infection and impairing mental health. Objective: To analyze the erectile function in Brazilian sample patients during pandemics with and without COVID-19 infection and compare with results from a sample obtained before the pandemic. Methods: Internet survey with epidemiologic questions, data on COVID-19 infection, and the International Index for Erectile Function (IIEF). Patients were divided into those with and without infections. A control group with results obtained before the pandemic was also included. Results: Four hundred twenty-two males were studied 210 with data obtained before the pandemic; 208 with data obtained during the pandemic (84 with COVID-19 infection and 124 without). Patients with COVID-19 infection had worse results of IIEF than those without (in the pandemics and before pandemics) with p=0.01 and used more sexual stimulants (p=0.02). The results were worse in the first month after the infection. Conclusion: Patients with COVID-19 infection had impairment in erectile function that is more severe in the first month after infection.